Potential of Regulation of Slum Area in The Village Meranti Pandak Pekanbaru City - Putri, LD; ., Harsini; Nasution, S R (International Journal of Engineering and Technology, 2018)
The slum area of Meranti Pandak is one of seven slum areas in Pekanbaru CityÂ according to Mayor's DecreeÂ No.Â 151/2016, is on the edge of the vulnerable Siak River with overflow due to ups and downsÂ .Â This study aims to produce a draft slum area design direction as one of the references for related parties to create Pekanbaru free from slum. The research method used is quantitative research method using secondary data as well as primary data with data collection techniques throughÂ observation and filling questionnaireÂ .Â Result of requirement analysis ofÂ structuringÂ slumsÂ areÂ the three aspectsÂ structuringÂ approachÂ settlement infrastructure;Â improvements toÂ environmental road accessibility,Â drinkingÂ water servicesÂ ,Â sanitation access fulfillment,wastewaterÂ management and waste management and fire hazard security,Â enhanced oversight of the development of settlement development from internal parties;Â LKM, TIPP, POKJA and internal resource team as well as from external parties;Â college,Â consult's,Â government and private sectors as well as community empowerment methods;Â counseling, mentoring and technical assistance.